Adsorption of Rhodamine B From Industrial Wastewater Using Bottom Ash Adsorbent from Palm Oil Mill Boiler Combustion: A Fixed-Bed Column Study - Rianda, Rizki; Maulana, Muhammad Zikri; Kurniawan, Meutia; Panjaitan, Muhammad Ishak Idrus; Salim, Muhammad Yahdi; Sylvia, Novi; Zulmiardi; Meriatna (Universitas Negeri Semarang, 2024)
Increased textile industry production increases water pollution, especially rhodamine B dyes that are difficult to degrade. Global efforts to reduce water pollution through the adsorption process have been carried out with various adsorbents, the utilization of bottom ash from palm oil mill boiler combustion waste is still very minimal. This study examines the effect of contact time and bottom ash adsorbent mass on the adsorption capacity and absorption efficiency of rhodamine B using a fixed bed column adsorption process. The results showed that the longer the adsorption time, the higher the absorption efficiency. In the rhodamine B adsorption process, the best absorption efficiency was 98.308% at 10 cm bed height for 120 minutes and the best absorption capacity was 0.474 mg/g at 12 cm bed height for 150 minutes. The R2 price of Langmuir isotherm was 0.9999. FTIR analysis showed the presence of -OH, C-H, C=C and C-O functional groups that play a role in the adsorption process. The surface area of bottom ash from SAA test was 94.517 m2 /g. The SEM-EDX test analysis results had dominant elements of C, O and Si which showed good adsorption activity. From the results of the study that bottom ash from the combustion of oil palm mill boilers can be used as an effective adsorbent in reducing rhodamine B.